Post‐seafloor spreading magmatism and associated magmatic hydrothermal systems in the Xisha uplift region, northwestern South China Sea. (8th February 2019) - Gao, Jinwei; Bangs, Nathan; Wu, Shiguo; Cai, Guanqiang; Han, Shuoshuo; Ma, Benjun; Wang, Jiliang; Xie, Yangbing; Huang, Wenkai; Dong, Dongdong; Wang, Dawei
Abstract: Submarine magmatism and associated hydrothermal fluid flows has significant feedback influence on the petroleum geology of sedimentary basins. This study uses new seismic profiles and multibeam bathymetric data to examine the morphology and internal architecture of post‐seafloor spreading magmatic structures, especially volcanoes of the Xisha uplift, in extensive detail. We discover for the first time hydrothermal systems derived from magmatism in the northwestern South China Sea. Numerous solitary volcanoes and volcanic groups occur in the Xisha uplift and produce distinct seismic reflections together with plutons. Sills and other localized amplitude anomalies were fed by extrusions/intrusions and associated fluid flow through fractures and sedimentary layers that may act as conduits for magma and fluid flows transport. Hydrothermal structures such as pipes and pockmarks mainly occur in the proximity of volcanoes or accompany volcanic groups. Pipes, pockmarks and localized amplitude anomalies mainly constitute the magmatic hydrothermal systems, which are probably driven by post‐seafloor spreading volcanoes/plutons. The hydrothermal fluid flows released by magma degassing or/and related boiling of pore fluids/metamorphic dehydration reactions in sediments produced local overpressures, which drove upward flow of fluid or horizontal flow into the sediments or even seafloor. Results show that post‐seafloor spreading magmatic activity is more intense during a 5.5 Ma event than one in 2.6 Ma, whereas the hydrothermal activities are more active during 2.6 Ma than in 5.5 Ma. Our analysis indicates that post‐seafloor spreading magmatism may have a significant effect on hydrocarbon maturation and gas hydrate formation in the Xisha uplift and adjacent petroliferous basins. Consequently the study presented here improves our understanding of hydrocarbon exploration in the northwestern South China Sea.